Former Yugoslav Republic of Macedonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The paper analyzes the export performance and external competitiveness in FYR Macedonia. It describes the trends in the account balance, external vulnerabilities, and different approaches to estimate the equilibrium real exchange rate; and reviews economic growth experience and prospects and reveals areas of weakness. It also discusses many different factors responsible for Macedonia's high unemployment rate and examines the main factors behind the low level of intermediation.